Analisis Pelaksanaan Perkawinan Adat Banjar Kalimantan Selatan di DKI Jakarta - Febyola Febyola; Jenny Sista Siregar; Lilis Jubaedah (Journal on Education, 2024)
The Banjar tribe has a tradition of being called "nyonya" which means wandering or migrating to various corners of the archipelago or abroad for business, preaching and studying. In the Nyonya show, the Banjar tribe community is influenced by various factors such as economic factors for survival, the need to study and preach. Migration of the Banjar tribe also occurred to Java. In this region, the Banjar tribe mixes with other tribes such as Arab-Indonesian, Gujarati, Malay, Bugi and local Javanese tribes. The development of the Banjar tribe on the island of Java is usually due to economic reasons (looking for a life in Banua Urang) and seeking knowledge. The method used in this research is qualitative which aims to find out the truth of all symptoms, variables or circumstances without testing certain hypotheses. Banjar traditional marriage has 3 (three) stages, namely before marriage, during marriage and after marriage. All expert informants expect and recommend carrying out the entire series in the Banjar traditional wedding ceremony, because each series contains meaning and cultural values that need to be preserved. This could be one way to preserve Banjar traditional culture, especially for the Banjar tribe people who live in DKI Jakarta. Even though they are overseas, they still have to remember their cultural origins. This is done so that the Banjar tribal people who are overseas can have knowledge about the origins of culture and the series of traditional Banjar marriage ceremonies, and the Banjar tribal people in DKI Jakarta are aware of the importance of maintaining and preserving the culture that has been handed down by their ancestors so that the values This culture is embedded in oneself and can be useful for future life.